Impact of non-invasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP) on risk of malignancy in patients undergoing lobectomy/thyroidectomy for suspected malignancy or malignant fine-needle aspiration cytology findings: a systematic review and meta-analysis. Issue 4 (October 2019) - Bongiovanni, Massimo; Faquin, William C; Giovanella, Luca; Durante, Cosimo; Kopp, Peter; Trimboli, Pierpaolo
Abstract : Objective: The second version of The Bethesda System for Reporting Thyroid Cytopathology endorsed the introduction of non-invasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP) as a distinct entity with low malignant potential into clinical practice. Consequently, the risk of malignancy (ROM) of cytological diagnoses has changed, but the magnitude of the change remains uncertain. The present systematic review was undertaken to obtain more robust information about the true impact of NIFTP on the ROM among patients undergoing surgery following a fine-needle aspiration cytology (FNAC) diagnosis of suspicious for malignancy (Bethesda V) or malignant (Bethesda VI). As they are managed surgically, these two diagnostic categories are the primary entities that are clinically impacted by the advent of NIFTP. Design: Systematic review and meta-analysis. Methods: A comprehensive literature search of online databases was performed in November 2018. The search was conducted looking for data of histologically proven NIFTP with preoperative FNAC. Results: One-hundred fifty-seven articles were identified and nine were included in the study. Overall, there were 13, 752 thyroidectomies with a cancer prevalence of 45.7%. When NIFTP was considered non-malignant, the pooled risk difference for ROM was 5.5%. Applying meta-analysis, the pooled prevalence of NIFTP among nodules with FNAC of Bethesda V or Bethesda VI was 14 and 3%, respectively. Conclusion: This meta-analysis shows that the inclusion of NIFTP leads to a reduction in the ROM for the Bethesda V and Bethesda VI FNAC diagnostic categories by 14 and 3%, respectively. Clinicians should be aware of these data to avoid overtreatment.